1945
DOI: 10.1021/ja01221a037
|View full text |Cite
|
Sign up to set email alerts
|

The Polymerization of Allyl Compounds. II. Preliminary Kinetic Study of the Peroxide-Induced Polymerization of Allyl Acetate

Abstract: Vol. 67 and a slow stream of carbon dioxide-free, dry nitrogen (or oxygen) was bubbled through the liquid, passed from there through two Dry Ice traps into a Dehydrite tube and finally into an Ascarite tube, the open end of which was protected by a soda-lime tube. The reaction vessel was kept at the boiling point of benzene for sixteen to twenty hours, then the system was swept with nitrogen for several hours until the Ascarite tube ceased to gain weight. Constancy was always attained in less than two hours. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

1962
1962
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(86 citation statements)
references
References 0 publications
1
85
0
Order By: Relevance
“…In allyl polymerization, the hydrogen atoms attached to the carbon atom alpha to the double bond, i.e., allylic hydrogens are responsible for facile chain transfer to monomer from reactive growing polymer radical to give resonance-stabilized monomeric allyl radical; it is well-known as ''degradative monomer chain transfer.'' 5 Recently, addition-fragmentation chain transfer is noted, 20 although the first reports of addition-fragmentation transfer agents in polymerization appeared in the late 1980's. [21][22][23] Allyl monomers could be very effective chain transfer agents, [24][25][26] although the main driving force for fragmentation is the weak single bond (CH 2 -X) of CH 2 ¼ CH-CH 2 X.…”
Section: Does Addition-fragmentation Chain Transfer Occur Significantly?mentioning
confidence: 99%
“…In allyl polymerization, the hydrogen atoms attached to the carbon atom alpha to the double bond, i.e., allylic hydrogens are responsible for facile chain transfer to monomer from reactive growing polymer radical to give resonance-stabilized monomeric allyl radical; it is well-known as ''degradative monomer chain transfer.'' 5 Recently, addition-fragmentation chain transfer is noted, 20 although the first reports of addition-fragmentation transfer agents in polymerization appeared in the late 1980's. [21][22][23] Allyl monomers could be very effective chain transfer agents, [24][25][26] although the main driving force for fragmentation is the weak single bond (CH 2 -X) of CH 2 ¼ CH-CH 2 X.…”
Section: Does Addition-fragmentation Chain Transfer Occur Significantly?mentioning
confidence: 99%
“…Thereafter, numerous reports on microgel formation in the homopolymerizations of multivinyl compounds and their copolymerizations with monovinyl monomers were published 7,[9][10][11][12] . However, no microgelation was observed in the bulk polymerization of diallyl phthalate (DAP) 13) giving a quite low primary chain length as a characteristic feature of allyl polymerization 14) , although Erath et al 1) observed directly the DAP cured resin as the agglomerate of colloidal particles by electron microscopy. These results suggested that the colloidal particles could be formed during the polymerization process beyond the gel point.…”
Section: Introductionmentioning
confidence: 99%
“…The adduct will react with a second ethyl radical, either directly, or through seine iilter~iiediate process (such as metathesis with diethyl ketone followed by reaction [5]). I11 all such cases ethyl radicals disappear from the system without the formation of CzHa or C4Hlo, and so the value of 114 falls below unity.…”
Section: T H E Icinetics Of Ti-ie Reactions O F T H E Ethyl Radicalmentioning
confidence: 99%
“…NIetathesis produces a new class of essential reaction of propagation in both allyl and vinyl polymerization. The experimental evidence for these views has been derived largely froin 1;inetic studies of the polymerization of allyl acetate (5)(6)(7)(8), and a comprehensive kinetic scheme has been proposed by Litt and Eirich (7).…”
Section: Introductionmentioning
confidence: 99%